2002
DOI: 10.1046/j.1365-3156.2002.00841.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the World Health Organization standard tourniquet test and a modified tourniquet test in the diagnosis of dengue infection in Viet Nam

Abstract: SummaryOBJECTIVES A positive tourniquet test is one of several clinical parameters considered by the World Health Organization to be important in the diagnosis of dengue haemorrhagic fever, but no formal evaluation of the test has been undertaken. As many doctors remain unconvinced of its usefulness, this study was designed to assess the diagnostic utility of both the standard test and a commonly employed modified test. METHODSMETHO DS A prospective evaluation of the standard sphygmomanometer cuff tourniquet t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(36 citation statements)
references
References 9 publications
4
29
2
1
Order By: Relevance
“…Similar studies have evaluated TT performance in different groups and places and have had similar results. A study in Vietnamese children reported a specifi city as high as 94% but a sensitivity of only 42% for the TT in diagnosing suspected dengue infection 19 . Another study, this time evaluating suspected dengue infection in adults in Laos, also reported high (84%) specifi city and low (34%) sensitivity 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Similar studies have evaluated TT performance in different groups and places and have had similar results. A study in Vietnamese children reported a specifi city as high as 94% but a sensitivity of only 42% for the TT in diagnosing suspected dengue infection 19 . Another study, this time evaluating suspected dengue infection in adults in Laos, also reported high (84%) specifi city and low (34%) sensitivity 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Esse método não foi realizado em todos os pacientes e apresentou positividade baixa. Isso pode indicar que acrescenta pouco ao diagnóstico de febre hemorrágica do dengue, sendo utilizado principalmente como indicador de presença de fragilidade vascular 9 . Sabe-se que a ocorrência de leucocitose no dengue pode ser considerada como um fator prognóstico associado ao desenvolvimento de complicações 14 .…”
Section: Discussionunclassified
“…A positive tourniquet test in this phase increases the probability of dengue. 7,8 In addition, these clinical features are indistinguishable between severe and nonsevere dengue cases. Therefore monitoring for warning signs and other clinical parameters is crucial to recognizing progression to the critical phase.…”
Section: Febrile Phasementioning
confidence: 99%